The transitional role of the Xhosa oral poet in contemporary South African society - Kaschula, Russell H (Rhodes University, Faculty of Humanities, School of Languages, 1991)
This thesis outlines the changing role of the Xhosa imbongi in contemporary South African society. The changing socio-economic and political scenario in South Africa, and the way in which the imbongi is adapting in order to accommodate new pressures created by these changes, form an integral part of this thesis. The effects of education and increasing literacy on the tradition are outlined. The interaction between oral and written forms is explored in chapter 2. The role of the imbongi within the religious sphere is included in chapter 3. Xhosa preachers within the independent churches often make use of the styles and techniques associated with oral poetry. Iimbongi who are not necessarily preachers also operate within this context. The relationship between the Congress of South African Trade Unions, the African National Congress and iimbongi has also been researched and forms part of chapters 4, 5, and the epilogue. The modern imbongi is drawn towards powerful organisations offering alternative leadership to many of the traditional chiefs. In the epilogue collected poetry is analysed in the context of Mandela's visit to Transkei in April 1990. Interviews have been conducted with chiefs, iimbongi attached to chiefs as well as those attached to different organisations. Poetry has been collected and analysed. In chapter 5, three case studies of modern iimbongi are included. The problems facing these iimbongi in their different contexts, as well as the power bases from which they draw, are outlined. Finally, an alternative definition of the imbongi is offered in the conclusion
Keywords: Folk poetry, Xhosa; Xhosa (African people) -- Religion; Xhosa (African people) -- Social life and customs; Xhosa poetry; Laudatory poetry